'Don't intervene, don't get involved': the Conservative Party's voluntarist approach to industrial relations and trade unionism, 1951–1964. Issue 3 (3rd July 2018) - Dorey, Peter
ABSTRACT: Britain's Conservative Party has traditionally had a reputation for being hostile towards the trade unions, but the period from 1951 to 1964 was remarkable for the extent to which most of the Conservative leadership sought to cultivate the trust and cooperation of Britain's trade unions. To the dismay of many on the Party's right, Conservative Ministers consistently refused to introduce industrial relations legislation or statutory curbs on the internal affairs and activities of the trade unions, insisting instead that the key to good industrial relations lay in improving 'human relations' and promoting partnership in industry. As these could not be achieved by invoking Acts of Parliament, Conservatives needed to pursue a more enlightened and patient approach to industrial relations and trade unionism.